2016
DOI: 10.20506/rst.35.3.2567
|View full text |Cite
|
Sign up to set email alerts
|

The impact of importation of live ruminants on the epizootiology of foot and mouth disease in Saudi Arabia

Abstract: Approximately five million live ruminants are imported annually into Saudi Arabia. The majority of these animals are imported shortly before the pilgrimage season from Sudan and the Horn of Africa, where foot and mouth disease (FMD) is known to be enzootic. This study was designed to investigate the impact of the importation of these live ruminants on the epizootiology of FMD in Saudi Arabia. The authors carried out antibody testing on a total of 480 sheep and 233 cattle from the sacrificial livestock yards of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Some countries such as Somaliland have economies that depend entirely on their livestock industries and employ over 70% of the population (5,6). Others such as the Kingdom of Saudi Arabia import 5 million live ruminants a year, most of which are sheep and goats (7). However, this economic value is directly dependent on animal health, which has been compromised in regions with high incidence of tick-borne diseases (8)(9)(10).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Some countries such as Somaliland have economies that depend entirely on their livestock industries and employ over 70% of the population (5,6). Others such as the Kingdom of Saudi Arabia import 5 million live ruminants a year, most of which are sheep and goats (7). However, this economic value is directly dependent on animal health, which has been compromised in regions with high incidence of tick-borne diseases (8)(9)(10).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Although various FMDV vaccines are available in most countries, ongoing outbreaks are still reported in some of these animal populations (Eble et al 2015). Also in Saudi Arabia, several FMDV outbreaks have been reported (Samuel et al 1988; Abd El-Rahim et al 2016; Mahmoud and Galbat 2017). One study during 1986–1987 reported the detection of serotype A in some animals from Saudi Arabia and Iran (Samuel et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed that the neither the vaccines used nor the vaccination interval used provided a high degree of protection for the herds against FMDV field infection (Woolhouse et al 1996). A new study evaluated the effects of importing large and small ruminants from Africa on the introduction of new FMDV strains to the Kingdom of Saudi Arabia (Abd El-Rahim et al 2016). They found that almost 50% of the tested sheep and cattle had FMDV antibodies (Abd El-Rahim et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some countries such as Somaliland have economies that depend entirely on their livestock industries and employ over 70% of the population (6,7). Others such as Saudi Arabia import 5 million live ruminants a year, most of which are sheep and goats (8). However, this economic value is directly dependent on animal health, which has been compromised in regions with high incidence of tick-borne diseases (9–11).…”
Section: Introductionmentioning
confidence: 99%